2021
DOI: 10.9734/ajrcs/2021/v6i430127
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming with Salicylic Acid (SA) and Hydrogen Peroxide (H2O2) Improve Germination and Seedling Growth of Wheat (Triticum aestivum) under Salt Stress

Abstract: Aim: Salinity is a major barrier to successful crop production. Seed priming and exogenous application of different signaling molecules can efficiently confer salinity tolerance. Wheat is a major cereal crop in the world and salinity drastically reduces the wheat seedling growth and yield. Therefore, the present study was conducted to explore the potentiality of different signaling molecules such as salicylic acid (SA) and H2O2 to alleviate the salinity-induced growth inhibition of wheat. Place and Durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Germination was enhanced in distilled water and KNO 3 @ 0.1%. The positive in uence of priming wheat seed in distilled water is in agreement with the ndings of (Tania et al 2021) and that of KNO 3 is in line with the report by (Salehzade et al 2009). Seeds primed with KNO 3 showed improved germination performance, early growth, and vigor index of wheat seedlings (Steiner et al 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Germination was enhanced in distilled water and KNO 3 @ 0.1%. The positive in uence of priming wheat seed in distilled water is in agreement with the ndings of (Tania et al 2021) and that of KNO 3 is in line with the report by (Salehzade et al 2009). Seeds primed with KNO 3 showed improved germination performance, early growth, and vigor index of wheat seedlings (Steiner et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…However, Salicylic acid @ 0.06% negatively in uenced the germination of wheat seed. Similarly, (Tania et al 2021) reported that wheat seed primed with 2 mM Salicylic acid for 30 minutes performed lower germination compared to the unprimed control under non-saline stress. Mannitol @ 2% resulted in lower and similar germination capacity with unprimed control.…”
Section: Discussionmentioning
confidence: 91%
“…One of the main types of stress that significantly reduces seed germination and crop establishment is salt stress. According to the literature, many crops like wheat, faba beans, and rice can acquire salinity resistance through priming and the addition of various signaling molecules [37][38][39]. The priming of maize seeds with GA 3 improved germination and seedling characteristics under salt stress, as we recently observed [40].…”
Section: Discussionmentioning
confidence: 86%
“…Seed germination and seedling establishment is very crucial for plant growth and productivity which often interrupted by some adverse conditions called stress like moisture, salinity, temperature, pathogen, weed, etc. Plants are known to be more tolerant when seeds are primed before being exposed to any stress [13][14]. In this study, it was investigated that seed priming could be helpful for faster and higher seed emergence, better survival and growth of rice seedlings when exposed to cold stress.…”
Section: Discussionmentioning
confidence: 99%